Onset of pulmonary stenosis after arterial switch operation for transposition of great arteries with intact ventricular septum - Delmo Walter, E M (EDIMES Edizioni Internazionali Srl, 2011)
INTRODUCTION: Pulmonary stenosis remains the most frequent complication and cause of reintervention after the arterial switch operation for transposition of the great arteries We investigated the onset, incidence, and outcome of pulmonary stenosis after arterial switch operation in neonates with transposition of the great arteries and intact ventricular septum. METHODS: Arterial switch operation using Lecompte maneuver was performed in 222 neonates with transposition of great arteries and intact ventricular septum. Complete medical records with serial echocardiograms were available for 174 (73%) patients and were reviewed for incidence of postoperative pulmonary stenosis defined as a thickened and doming pulmonary valve and/or a pressure gradient of >25 mmHg. RESULTS: During a mean follow-up of 14.4 ± 0.54 years, 31 children developed pulmonary stenosis. Onset of significant stenosis occurred as early as 30 days and as late as 10 years after arterial switch operation. Uncomplicated interventional balloon/stent angioplasty was performed in 11 patients with supravalvular stenosis (mean pressure gradients of 65 mmHg). Severe restenosis occurred in these patients post-angioplasty (range 2-7 years). In other 10 patientseither patch enlargement of the area involved or angioplasty were performed. Freedom from intervention was 68.6±8.7% at 1 year and 42.8.1±9.5% at 15 years and onwards. CONCLUSION: Over time, pulmonary stenosis developed after arterial switch operation. Balloon angioplasty for supravalvular pulmonary stenosis could be the initial treatment of choice owing to the high success rate. Surgical intervention is offered to those with pulmonary valve stenosis having pressure gradients of >50 mmHg, and for re-stenosis after intervention/stent implantation.